Comparison of two brief mindfulness interventions for anxiety, stress and burnout in mental health professionals: a randomised crossover trial - Ruiz-Íñiguez, Raquel; Carralero Montero, Ana; Burgos-Julián, Francisco A.; Fabelo Roche, Justo R.; Santed, Miguel Á. (Frontiers in Psychology, 2023)
Background: Anxiety, stress and burnout are a growing reality among mental health professionals, impacting negatively on them and their clients. Mindfulness-based interventions (MBIs) have demonstrated effectiveness in mitigating these sufferings. Nevertheless, there is a lack of knowledge on the impact of MBIs in Cuba. Objectives: To compare the effectiveness of two brief mindfulness-based interventions for reducing anxiety, work stress and burnout. Methods: A total of 104 mental health professionals from Havana (Cuba) participated in a randomised crossover trial. Group A received first an intervention involving body-centred practices (body scan and Hatha yoga) and a second intervention involving mind-centred practices (focused attention and open monitoring meditation). Group B received the same interventions but in reverse order. Four measures (anxiety, stress, burnout syndrome, and antecedents of burnout) were measured at baseline, posttest1, posttest2, and 6-months follow-up. Results: After the first intervention, there was a between-group difference for burnout syndrome, but the ES was similar for both groups. After the second intervention (implementing both practises), groups showed the largest effect sizes, and there was a between-group difference for antecedents of burnout. Results were partially maintained at six-month follow-up. Conclusions: These results suggest that mind-centred practises can be as effective as body-centred practises for stress, anxiety and burnout reduction. The combination of both types of practises could be the most effective way of teaching mindfulness. About the sequence of implementation, teaching mind-centred practises first and then body-centred practises could be most effective for reducing antecedents of burnout. Trial registration number NCT03296254 (clinicaltrials.gov).